(untitled) (Research, Society and Development, 2021)
Objective: To describe the epidemiological aspects of meningitis in Northeast brazilian in 2019. Methods: This is a descriptive, retrospective study with a quantitative approach developed through the Sistema de Informação de Agravos de Notificação linked to the Departamento de Informática do Sistema Único de Saúde. The variables collected for the construction of this research were: the state from the cases (including only cases from the Northeast region), sex, race/color, age group, etiology of the confirmed cases and the outcome. Results: In the year investigated, 2.487 cases of meningitis were reported in Northeast brazilian. Among the states in the region, Pernambuco had the highest number of cases, followed by Ceará and Bahia. Among the individuals affected by the pathology, there was a prevalence of males in 60,64% of the cases. There was a greater manifestation in young adults aged 20 to 39 years, which represented 25,81% of the total cases. The increase was seen in 76% of cases. Viral meningitis was observed as the most prevalent form, representing 38,16% of cases. Conclusion: The data presented here are relevant. Even with the existence of free immunization offered by the Sistema Único de Saúde for the most common etiologic agents of meningitis, cases in the Northeast brazilian continue to occur. It is also relevant to draw attention to underreporting, with the existence of cases that are not reported to the competent authorities.